The Meaning of the Butterfly in Wang Meng’s Novel Butterfly - Ungkitphaiboon, Chollada; Prapantamit, Wuttipong (FOYER: The Journal of Humanities, Social Sciences, and Education, 2023)
Literature is a reflection of the author’s perspective on the society of the time, which is often hidden by the author’s intended meaning or message to the reader. This article aims to study and analyze the hidden meaning of the "butterfly" in Wang Meng’s Butterfly, a work of fiction that reflects Chinese political society between 1949 and 1997, through the lens of Lakoff and Johnson’s Conceptual Metaphor Theory (1980). In Wang Meng’s works, the "butterfly" not only alludes to actual animals, but also reflects the “meaning of the butterfly in Zhuangzi philosophy” in three fundamental principles: 1) independence, 2) change, and 3) the oneness of all. In addition, the "butterfly" reflects the life of the protagonist, Zhang Shiyuan, a former adherent of both the left and the right political ideologies, which leads to the image of his life flowing from the highest point to the bottom.